Device-associated infections and patterns of antimicrobial resistance in a medical-surgical intensive care unit in a University Hospital in Thailand - Thongpiyapoom S. (2014)
Background: Surveillance of nosocomial infection in the intensive care unit (ICU) received a high level of attention and outcome indicators are now used in benchmarking the quality of patient care. Since 1999 the surveillance has targeted three site-specific, device-associated infections, including ventilator-associated pneumonia (VAP), central-line-related bloodstream infection (CR-BSI), and catheter-related urinary tract infection (CR-UTI). The authors conducted a two-year prospective study on the incidences of these infections acquired in an ICU and report herein, together with the antibiotic susceptibility patterns of the microorganisms isolated in an ICU. Patients and Method: Continuous prospective data collection was conducted on patients admitted to an adult medical-surgical ICU of a university hospital in Thailand from June 2000 to May 2002. Results: A total 1422 patients with a total of 9370 patient-days were enrolled in the study. The incidence of VAP, CR-BSI, and CR-UTI were 10.8/1000 ventilator-days (95%C.I: 8.5-13.6), 2.6/1000 central-line-days (95%C.I: 1.5-4.4), and 13.8/1000 urinary-catheter-days (95%C.I: 10.7-17.5) respectively. The most common causative pathogens were Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae. The proportion of methicillin-resistant Staphylococcus aureus, imipenem-resistant P. aeruginosa, ceftazidime-resistant A. baumannii, third-generation-cephalosporin-resistant K. pneumoniae, and quinolone-resistant E. coli were 68.8%, 30.9%, 68.5%, 44.6%, 38.3% respectively. Conclusion: The incidences of VAP and CR-BSI were comparable to the National Nosocomial Infection Surveillance (NNIS) report. But the incidence of CR-UTI was over the 90th percentile. The antibiotic resistance had become a serious problem.